(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2021)
Public relations and its practices are perceived to have a direct role in working towards managing and improving foreign relations, and is instrumental in the implementation of larger and more inclusive foreign policies. To justify the connection between public relations and foreign affairs of India, the following research paper defines the conceptual role of public relations in India’s foreign policy-making and implementation. The paper explains how public relations functions helped India to open the lines of communication between India and its foreign allies and create a space for itself in the global environment. The study examines the key incidents in the foreign policy actions and developments in India and analysed them on the basis of the strategic application of the tools of public relations. The findings reveal the strategic role of public relations in the development of foreign relations of India and how the government has successfully worked in a two-way symmetrical format for developing and implementing its foreign policy initiative.